Increased Endothelial Progenitor Cell Number in Early Stage of Endometrial Cancer - Paprocka, Maria; Kieda, Claudine; Kantor, Aneta; Bielawska-Pohl, Aleksandra; Dus, Danuta; Czekanski, Andrzej; Heimrath, Jerzy (International journal of gynecological cancer, 2017)
It is generally believed that circulating endothelial cells (CECs) and endothelial progenitor cells (EPCs) reflect the state of the endothelium, its injury and/or repair possibilities. In different types of cancers, increased numbers of CECs and EPCs were found, suggesting their participation in cancer angiogenesis. The objective of this study was to determine whether, in the blood circulation of women with early endometrial cancer, CEC and EPC levels differ from those of healthy women of similar age. For CEC number evaluation, samples of peripheral blood cells of women with endometrial carcinoma and control subjects were labeled with anti-CD31 and anti-CD45 antibodies; for EPCs, with anti-VEGFR2 (vascular-endothelium growth factor receptor 2)/KDR and anti-CD34 antibodies. The CEC and EPC cells were then quantified by flow cytometry. Endothelial progenitor cell numbers (CD34, VEGFR2/KDR) in the peripheral blood of women with endometrial carcinoma were significantly augmented as compared with those of control healthy women and CEC numbers (CD31, CD45) were similar in both groups. Cancer patients were divided according to the grading into G1 and G2 groups and according to the stage into International Federation of Gynecology and Obstetrics (FIGO) stage IA and FIGO IB groups. Statistically significant augmented EPC numbers were demonstrated only in G1 and FIGO IA patients. These results strongly suggest new vessel formation from recruited endothelial precursors as being involved mainly at the early stages of tumor progression.